The Ramayan and Other Oral Narratives of the Kunknas - Dahyabhai Vadhu (My University, 2012)
The Ramayan and Tales of the Kunknas Adivasis of Dang in south Gujarat. The volume offers a glimpse into the richness of tribal imagination and the deep connections between the mainstream and tribal literary traditions.
Keywords: English